Method for preparing graphite electrode through secondary impregnation

Through the secondary impregnation preparation method, the graphite electrode is impregnated with the impregnated slurry of antioxidants and binders to form a dense protective layer, which solves the problem of shortening service life and increasing cost of graphite electrodes in high temperature and high current environments, and achieves higher oxidation resistance and mechanical strength.

CN119684000AInactive Publication Date: 2025-03-25LILUO CITY YIFENG CARBON MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411746737.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing graphite electrodes are prone to fracture and peeling caused by erosion, oxidative evaporation, mechanical and thermal stress in high temperature and high current environments, resulting in shortening of service life and increasing cost.

Method used

Using the secondary impregnation preparation method, a special impregnation slurry, including antioxidants and binders, is used to form a dense protective layer through impregnation of the inner and outer layers, and improve the antioxidant performance and mechanical strength of the graphite electrode.

Benefits of technology

It significantly enhances the oxidation resistance and mechanical strength of graphite electrodes, extends service life, reduces energy consumption and improves production efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a graphite electrode by secondary impregnation, the method comprises the following steps: firstly, respectively preparing two impregnation slurries, the two impregnation slurries are composed of dry materials, binders and antioxidants in different proportions, and during preparation, preheating the dry materials, dry-mixing, adding the antioxidants, heating the binders and wet-mixing in sequence until uniform paste is formed; the preparation method comprises the following steps: performing surface roughening treatment on a graphite electrode green body, performing inner-layer impregnation by using first impregnation slurry, performing outer-layer impregnation by using second impregnation slurry, and performing drying treatment after each impregnation; and after dipping and drying, sintering and graphitizing the graphite electrode green body in sequence to obtain a graphitized product, and post-processing the graphitized product to obtain a final graphite electrode product. The problem that in the prior art, a graphite electrode is prone to loss in the using process is effectively solved, the service life of the graphite electrode is prolonged on the basis that the using performance of the graphite electrode is guaranteed, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphite electrode in carbon material technology, in particular to a method for preparing a graphite electrode by secondary impregnation suitable for an industrial furnace. Background Art

[0002] Conductive electrodes are indispensable conductive materials in the processes of electric arc furnace steelmaking, industrial furnace smelting of yellow phosphorus, industrial silicon, zinc, etc. They are mainly divided into electrode paste, carbon electrode, graphite electrode and other types. With the large-scale trend of industrial furnaces and the continuous increase in input power, the quality requirements for conductive electrodes are becoming increasingly stringent. In the application of large industrial furnaces, low-end products such as traditional electrode paste and carbon electrodes are gradually being eliminated. In contrast, graphite electrodes, with their excellent conductivity and low thermal expansion coefficient, significantly reduce consumption during use, and are therefore gradually becoming the leading product in the market. According to different quality indicators, graphite electrodes can be further subdivided into ordinary power graphite electrodes, high power graphite electrodes and ultra-high power graphite electrodes. Among them, ultra-high power graphite electrodes are mainly used in electric arc furnace steelmaking.

[0003] As industrial furnaces develop towards larger sizes and higher powers, electric arc furnaces with larger capacities, higher currents and voltages have begun to be widely used. In order to reduce consumption and improve technical and economic indicators, higher performance requirements are placed on graphite electrodes.

[0004] In the prior art, the loss of graphite electrodes in industrial furnaces is mainly reflected in

[0005] 1. Erosion and consumption caused by contact between smelting slag and electrodes;

[0006] Second, due to the evaporation and oxidation loss of the electrode surface under the high temperature of the arc, and as the temperature increases, the oxidation rate increases, which will further accelerate the loss of the graphite electrode;

[0007] 3. Fracture and peeling of the electrode due to mechanical and thermal stress during use;

[0008] The above unfavorable factors work together to shorten the service life of graphite electrodes and increase the cost of use. At present, in order to alleviate the impact of these factors on graphite electrodes, in addition to improving the raw materials and preparation process of graphite electrodes, common graphite electrode protection methods mainly include adding protective agents during the graphite electrode forming process and forming a protective film layer on the surface of the graphite electrode. Among them, the treatment method of adding protective agents during the graphite electrode forming process will reduce the conductivity of the graphite electrode to a certain extent, thereby affecting its performance. The forming methods of the protective layer include metallized film layer, coating and impregnation of anti-oxidation coating. The metallized film method is prone to interlayer peeling due to the mismatch between the thermal expansion coefficient of the metal coating and the electrode material under high temperature environment, which will reduce the stability of the interface area and cause peeling problems; only coating the oxidation coating also faces stability challenges; although the impregnation anti-oxidation coating method is better than the metallized film in terms of structural stability, its protection effect is limited by the impregnation material and process, and when the graphite electrode is subjected to thermal stress deformation, it is still prone to local cracks and peeling.

[0009] Therefore, in order to overcome these technical challenges, it is necessary to develop an innovative optimization process to improve the oxidation resistance and mechanical strength of graphite electrodes, thereby extending their service life. Summary of the invention

[0010] The technical problem solved by the present invention is to provide a method for preparing graphite electrodes by secondary impregnation to solve the shortcomings of the above-mentioned background technology.

[0011] The technical problem solved by the present invention is achieved by adopting the following technical solutions:

[0012] A method for preparing a graphite electrode by secondary impregnation is used for optimizing the graphite electrode green body to improve its stability and durability under high temperature and high current environment; the method comprises the following steps:

[0013] Preparing the impregnation slurry: the impregnation slurry includes a first impregnation slurry for impregnating the inner layer and a second impregnation slurry for impregnating the outer layer;

[0014] The first impregnation slurry comprises 100-120 parts by weight of dry material, 35-45 parts by weight of binder, and 1-3 parts by weight of antioxidant; the dry material comprises 50-70wt% of petroleum coke, 20-40wt% of graphite chips, and 1-10wt% of raw chips; the binder is medium-temperature coal tar pitch or medium-temperature modified asphalt; the antioxidant is a composition of metal oxide, metal carbide, and metal boride in a mass ratio of 3:1:1; during preparation, the dry material is first preheated to 80-90°C, added to a kneading pot for dry mixing, and after mixing evenly, the antioxidant is added and stirred, and after stirring evenly, the binder is taken and heated to a melted state, and the softened binder is wet mixed with the dry mixture until a uniform paste is formed, so as to obtain the first impregnation slurry;

[0015] The second impregnation slurry comprises 60-80 parts by weight of dry material, 25-35 parts by weight of binder and 7-15 parts by weight of low-quinoline medium-temperature coal tar pitch; the dry material comprises 30-50wt% of petroleum coke, 40-60wt% of graphite chips and 1-5wt% of raw chips, and the binder is medium-temperature coal tar pitch or medium-temperature modified asphalt; when preparing the second impregnation slurry, first preheat the dry material to 80-90°C, add it to a kneading pot for dry mixing, and after mixing evenly, take the binder and the low-quinoline medium-temperature coal tar pitch and heat them together until they are melted, and wet mix the softened binder with the dry mixture until a uniform paste is formed, so as to obtain the second impregnation slurry;

[0016] Impregnation treatment: The surface of the graphite electrode green body is roughened, and after the treatment, the graphite electrode green body is placed in an impregnation tank; first, the inner layer is impregnated, that is, the green body is impregnated with the first impregnation slurry, and after the impregnation is completed, it is taken out and dried; then the outer layer is impregnated, that is, the green body that has been impregnated with the inner layer is impregnated with the second impregnation slurry, and after the impregnation is completed, it is taken out and dried;

[0017] Drying treatment: Place the impregnated graphite electrode green body in a drying furnace for drying. The drying temperature is controlled at 100-120°C and the drying time is controlled at 12-24 hours to ensure that the solvent in the impregnation slurry is completely volatilized to form a uniform and dense impregnation layer.

[0018] Sintering treatment: Place the dried graphite electrode green body in a sintering furnace for sintering. The sintering temperature is controlled at 1000-1200°C and the sintering time is controlled at 8-12 hours to ensure that the impregnation layer and the graphite electrode green body are fully combined to form a stable structure.

[0019] Graphitization: Place the calcined product in an Acheson graphitization furnace and perform graphitization treatment according to the set power transmission curve, heat the temperature to 2500-3000°C, control the graphitization time to 10-20 hours, and then cool it to room temperature with the furnace and keep it for 150-300 hours to obtain a graphitized product;

[0020] Cooling treatment: The obtained graphitized product is taken out from the Acheson graphitization furnace for trimming treatment to remove impurities and excess attached to the surface to obtain the final graphite electrode product.

[0021] As a further limitation, when preparing the impregnation slurry, the particle sizes of petroleum coke and graphite used as dry materials in the first impregnation slurry and the second impregnation slurry should be controlled between 100-200 mesh and 200-300 mesh, respectively, to ensure the uniformity of the slurry and the impregnation effect.

[0022] As a further limitation, when preparing the impregnation slurry, the technical parameters of the medium-temperature coal tar or medium-temperature modified asphalt used as the dry material in the first impregnation slurry and the second impregnation slurry are a softening point between 80 and 120°C and a needle penetration between 10 and 30, so as to ensure that the impregnation slurry has good fluidity and impregnation ability.

[0023] As a further limitation, when preparing the impregnation slurry, the oxide in the corresponding antioxidant is one or a combination of aluminum oxide, magnesium oxide, silicon oxide, and titanium oxide, the carbide is silicon carbide or boron carbide or a combination of the two, and the boride is titanium boride or zirconium boride or a combination of the two.

[0024] As a further limitation, in the stage of preparing the impregnation slurry, the viscosity of the obtained first impregnation slurry is between 3000mPa·S and 6000mPa·S; and the viscosity of the first impregnation slurry is between 1000mPa·S and 3000mPa·S.

[0025] As a further limitation, during the impregnation process, the surface roughening of the graphite electrode green body can be achieved by methods such as sandblasting, mechanical grinding or chemical etching to increase the roughness of the green body surface, thereby improving the bonding strength between the impregnation slurry and the green body.

[0026] As a further limitation, during the impregnation process, after the inner layer is impregnated with the first impregnation slurry and the outer layer is impregnated with the second impregnation slurry, the impregnation pressure and the impregnation time are different: during the inner layer impregnation, the impregnation pressure should be controlled at 0.1-0.3MPa, and the impregnation treatment time is 12-18 hours to ensure that the slurry can fully penetrate into the internal structure of the graphite electrode green body, and after the outer layer impregnation, the impregnation pressure should be appropriately increased to 0.3-0.5MPa, and the impregnation treatment time is 32-45 hours to form a denser outer protective film to effectively resist the erosion of the external environment.

[0027] As a further limitation, during the impregnation process, after the inner layer is impregnated with the first impregnation slurry and the outer layer is impregnated with the second impregnation slurry, a mold can be used to cold press and hold the outside of the impregnated graphite electrode green body. During the cold pressing and holding, the corresponding mold temperature is lower than 60°C, the pressure is controlled at 0.5-1.0MPa, and the cold pressing holding time is controlled at 1-3 hours.

[0028] As a further limitation, during the drying process, an inert atmosphere is used in the drying furnace to ensure the quality of the electrode. The drying temperature set in the drying furnace should be controlled between 100 and 150° C., and the drying time is 9 to 12 hours.

[0029] Beneficial effects: The present invention relates to a method for preparing graphite electrodes by secondary impregnation. The secondary impregnation process ensures uniform impregnation effect inside and outside the graphite electrode, which not only improves the mechanical strength of the electrode, but also significantly enhances its antioxidant properties. By adding specific antioxidants to the impregnation slurry, the stability of the graphite electrode in a high temperature environment is further enhanced, and the loss caused by oxidation is effectively reduced. It ensures that the impregnation slurry can fully penetrate into the internal structure of the graphite electrode, forming a tighter protective layer, which effectively resists the erosion of the external environment. The conductivity of the graphite electrode is further enhanced, and its application in industrial furnaces can significantly reduce energy consumption and improve production efficiency. DETAILED DESCRIPTION

[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0031] In the following embodiments, it will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as the general understanding of those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as the meaning in the context of the prior art, and will not be interpreted with an idealized or overly formal meaning unless defined as herein.

[0032] The steps of preparing a graphite electrode by secondary impregnation are as follows:

[0033] First prepare the raw materials:

[0034] The graphite electrode blank as one of the raw materials can be a homemade graphite electrode or a finished graphite electrode purchased from the market. Both the homemade graphite electrode and the commercially available finished graphite electrode are graphite electrodes without coating and without impregnation treatment. In this embodiment, a homemade graphite electrode is used.

[0035] Then prepare:

[0036] The petroleum coke, graphite chips and raw chips as dry material components, the corresponding petroleum coke and graphite chips are crushed and powdered respectively to obtain two groups of 120-180 mesh and 240-280 mesh. Among them, the group of 120-180 mesh is used to prepare the first impregnation slurry, and the group of 240-280 mesh is used to prepare the second impregnation slurry to ensure the uniformity and impregnation effect of different slurries; the raw chips are waste materials generated in the production process of carbon processing enterprises, the paste residue dropped during the molding process, and the residual chips cut off during extrusion molding. After crushing and powdering, the particle size is controlled to be 240-280 mesh.

[0037] The medium-temperature coal tar used as a binder has a softening point of 90°C and a needle penetration of 28.

[0038] Low-quinoline medium-temperature coal tar pitch as an adhesive bonding component;

[0039] The antioxidant mixture is a mixture of metal oxide, metal carbide and metal boride in a mass ratio of 3:1:1, the corresponding metal oxide is a mixture of aluminum oxide and magnesium oxide in a mass ratio of 1:1, the metal carbide is silicon carbide, and the boride is a mixture of titanium boride and zirconium boride in a mass ratio of 3:1.

[0040] In Example 1, the graphite electrode which is strengthened by the secondary impregnation treatment is obtained by the following method:

[0041] First, the impregnation slurry is prepared. The preparation of the impregnation slurry includes preparing a first impregnation slurry and a second impregnation slurry. The preparation of the first impregnation slurry and the second impregnation slurry can be carried out simultaneously or separately.

[0042] When preparing the first impregnation slurry, first mix 7kg of petroleum coke, 2kg of graphite chips and 1kg of raw chips according to mass parts, preheat to 80-90°C and add them into a kneading pot for dry mixing, add 300g of antioxidant after mixing evenly and keep stirring, take 3.5kg of medium-temperature coal tar as a binder and heat it to a melted state after stirring evenly, wet mix the softened binder with the dry mixture until a uniform paste is formed, and obtain the first impregnation slurry; the viscosity of the prepared first impregnation slurry is between 4500 and 5000mPa·S.

[0043] When preparing the second impregnation slurry, first, 3kg of petroleum coke, 4kg of graphite chips and 1kg of raw chips are mixed according to mass parts, preheated to 80-90°C, and added into a kneading pot for dry mixing. After mixing evenly, 2.75kg of medium-temperature coal tar and 1.5kg of low-quinoline medium-temperature coal tar are heated to a melted state, and the softened wet mixture is combined with the dry mixture for wet mixing until a uniform paste is formed to obtain the second impregnation slurry; the viscosity of the prepared second impregnation slurry is between 1500 and 1800 mPa·S.

[0044] In the impregnation slurry, the dry material plays the role of filling and reinforcing. It can improve the conductivity and mechanical strength of the electrode after impregnation by forming a dense protective layer on the surface of the electrode, while also enhancing the corrosion resistance and thermal shock resistance of the electrode. The binder is responsible for tightly bonding the dry material particles to form a stable structure and ensure the uniform distribution of the impregnation slurry inside the electrode. The introduction of the dispersant helps to improve the fluidity of the slurry and prevent particle aggregation, thereby ensuring the uniformity of the impregnation process. The addition of antioxidants is to further enhance the antioxidant capacity of the electrode and reduce the performance degradation caused by oxidation in high-temperature use environments.

[0045] Next, the impregnation treatment is carried out. First, the surface of the graphite electrode green body is sandblasted to increase its surface roughness, thereby improving the bonding strength between the impregnation slurry and the green body to ensure that the impregnation slurry can fully penetrate into the interior of the electrode.

[0046] Subsequently, the treated graphite electrode blank is placed in the impregnation tank, and the inner layer impregnation procedure is performed first. This procedure uses the first impregnation slurry, the impregnation pressure is maintained at 0.3MPa, and it lasts for 12 hours. After the inner layer impregnation is completed, the graphite electrode blank is taken out and dried, and an inert atmosphere is maintained in the drying furnace. The drying temperature is set to 120°C and the drying time is also 12 hours to ensure that the solvent in the slurry is completely evaporated, thereby forming a uniform and dense impregnation layer; the purpose of the inner layer impregnation is to enhance the internal structure of the electrode and improve its antioxidant properties at high temperatures. Next is the outer layer impregnation, using the second impregnation slurry, the impregnation pressure is increased to 0.5MPa, and the treatment time is extended to 40 hours. The second impregnation slurry can further enhance the surface oxidation resistance and mechanical strength of the electrode. At the same time, the second impregnation slurry is close to the first impregnation slurry in polarity, and it is not easy to peel off on the surface of the first impregnation slurry due to the unevenness of the impregnation slurry. At the same time, it can also ensure that the second impregnation slurry and the first impregnation slurry can penetrate each other to produce a mixed interface with higher strength, avoiding external bumps and thermal stress shocks. Damage to the electrode surface. After the outer layer is impregnated, the same drying procedure as after the inner layer is impregnated is performed again to remove excess impregnation slurry. Through the secondary impregnation, the surface and internal structure of the graphite electrode are further optimized, thereby showing better stability and durability under high temperature and high current environments.

[0047] After the drying process is completed, the graphite electrode blank is placed in a sintering furnace for sintering. During sintering, the sintering furnace is controlled to be in an inert atmosphere, the temperature is controlled at 1150°C, and the sintering time is controlled at 10 hours to ensure that the impregnation layer and the graphite electrode blank are fully combined to form a stable structure; the sintering process is to make the impregnation slurry form a stable structure inside the electrode, and the sintering process is usually carried out at a high temperature to ensure that the impregnation slurry can be fully solidified, thereby improving the overall performance of the electrode.

[0048] After the sintering treatment is completed, the baked product is placed in the Acheson graphitization furnace and graphitized according to the set power transmission curve. The temperature is heated to 3000°C, the graphitization time is controlled to 10 hours, and then the furnace is cooled to room temperature and maintained for 240 hours to obtain a graphitized product. The obtained graphitized product is taken out of the Acheson graphitization furnace for blanking treatment, and the impurities and excess attached to the surface are removed to obtain the final graphite electrode product.

[0049] In Example 2, the graphite electrode which has been subjected to a secondary impregnation treatment to be strengthened is obtained by the following method:

[0050] First, the impregnation slurry was prepared: When preparing the first impregnation slurry, the same method as in Example 1 was used, but different mass proportions were used, specifically 6 kg of petroleum coke, 3 kg of graphite chips and 0.5 kg of raw chips, and 250 g of antioxidant. The amount of medium-temperature coal tar was 3.2 kg, and the viscosity of the prepared first impregnation slurry was between 4000 and 4500 mPa·S.

[0051] When preparing the second impregnation slurry, the same method as in Example 1 was used, but different mass proportions were used, specifically 4 kg of petroleum coke, 5 kg of graphite chips and 400 g of raw chips. The amount of medium-temperature coal tar was 3 kg, and the amount of low-quinoline medium-temperature coal tar was 1.25 kg. The viscosity of the prepared second impregnation slurry was between 1200 and 1500 mPa·S.

[0052] Next, the impregnation treatment is carried out. Similarly, the surface of the graphite electrode blank is first sandblasted to increase its surface roughness. The treated graphite electrode blank is placed in the impregnation tank, and the inner layer impregnation procedure is performed first. This procedure uses the first impregnation slurry, and the impregnation pressure is maintained at 0.25MPa for 15 hours. After the inner layer impregnation is completed, the graphite electrode blank is taken out and dried, and an inert atmosphere is maintained in the drying furnace. The drying temperature is set to 110°C and the drying time is 12 hours; next is the outer layer impregnation, using the second impregnation slurry, the impregnation pressure is increased to 0.4MPa, and the treatment time is extended to 35 hours. After the outer layer impregnation is completed, the same drying procedure as after the inner layer impregnation is performed again.

[0053] After the drying treatment is completed, the graphite electrode blank is placed in a sintering furnace for sintering. During sintering, the sintering furnace is controlled to be in an inert atmosphere, the temperature is controlled at 1100°C, and the sintering time is controlled at 12 hours. After the sintering treatment is completed, the baked product is placed in an Acheson graphitization furnace, and graphitization treatment is performed according to the set power transmission curve, the temperature is heated to 2800°C, the graphitization time is controlled at 12 hours, and then the furnace is cooled to room temperature and maintained for 200 hours to obtain a graphitized product. The obtained graphitized product is taken out of the Acheson graphitization furnace for blank repair treatment, and impurities and excess attached to the surface are removed to obtain the final graphite electrode product.

[0054] In Example 3, the graphite electrode which has been subjected to a secondary impregnation treatment to be strengthened is obtained by the following method:

[0055] First, prepare an impregnation slurry;

[0056] When preparing the first impregnation slurry, the same method as in Example 1 was used, but different mass proportions were used, specifically 5.5 kg of petroleum coke, 4 kg of graphite chips and 500 g of raw chips, and 250 g of antioxidant. The amount of medium-temperature coal tar was 4 kg, and the viscosity of the prepared first impregnation slurry was between 4200 and 4700 mPa·S.

[0057] When preparing the second impregnation slurry, the same method as in Example 1 was used, but different mass proportions were used, specifically 5 kg of petroleum coke, 4 kg of graphite chips and 300 g of raw chips. The amount of medium-temperature coal tar was 2.75 kg, and the amount of low-quinoline medium-temperature coal tar was 1.25 kg. The viscosity of the prepared second impregnation slurry was between 1300 and 1600 mPa·S.

[0058] Next, the impregnation treatment is carried out. The surface of the graphite electrode blank is also firstly sandblasted to increase its surface roughness. The treated graphite electrode blank is placed in the impregnation tank, and the inner layer impregnation procedure is first performed. The procedure uses the first impregnation slurry, and the impregnation pressure is maintained at 0.28MPa for 14 hours. After the inner layer impregnation is completed, the mold is used to cold press and hold the outer side of the impregnated graphite electrode green body. The corresponding mold temperature during cold pressing is lower than 60°C, and the pressure is controlled to be 0.8MPa. After cold pressing for 1 hour, the graphite electrode blank is taken out and dried, and an inert atmosphere is maintained in the drying furnace. The drying temperature is set to 115°C and the drying time is 12 hours; the next step is the outer layer impregnation, using the second impregnation slurry, the impregnation pressure is increased to 0.45MPa, and the processing time is extended to 38 hours. After the outer layer impregnation is completed, the mold is also used to cold press and hold the outer side of the impregnated graphite electrode green body. The corresponding mold temperature during cold pressing is lower than 60°C, and the pressure is controlled to be 1MPa. After cold pressing for 2 hours, the graphite electrode blank is taken out and the same drying procedure as after the inner layer impregnation is performed again.

[0059] After the drying treatment is completed, the graphite electrode blank is placed in a sintering furnace for sintering. During sintering, the sintering furnace is controlled to be in an inert atmosphere, the temperature is controlled at 1125°C, and the sintering time is controlled at 11 hours. After the sintering treatment is completed, the baked product is placed in an Acheson graphitization furnace, and graphitization treatment is performed according to the set power transmission curve, the temperature is heated to 2900°C, the graphitization time is controlled at 11 hours, and then the furnace is cooled to room temperature and maintained for 220 hours to obtain a graphitized product. The obtained graphitized product is taken out of the Acheson graphitization furnace for blank repair treatment, and impurities and excess attached to the surface are removed to obtain the final graphite electrode product.

[0060] The graphite electrodes prepared in the above three embodiments of this embodiment first perform inner layer impregnation on the graphite electrode green body with surface roughening treatment, use the first impregnation slurry to fill the pores inside the electrode, and then perform outer layer impregnation, and use the second impregnation slurry to immerse the electrode surface again in a specific impregnating agent to form a protective film. The graphite electrode treated with the second impregnation shows higher thermal shock resistance and mechanical impact resistance during use. In addition, since the impregnating agent forms a protective film on the electrode surface, the oxidation and evaporation loss of the electrode surface can be effectively reduced. Compared with the homemade graphite electrode that has not been impregnated, it has significantly improved mechanical strength and antioxidant properties, and its stability in high temperature environment has also been enhanced. Its average service life can be increased by 20 to 50% under the same working conditions set in the laboratory.

[0061] Its internal structure achieves more uniform filling, forming a denser protective layer, which effectively resists erosion from the external environment. In addition, by adding specific antioxidants to the impregnation slurry, the stability of the graphite electrode in a high temperature environment is further improved, effectively reducing the loss caused by oxidation. The method of preparing a graphite electrode by secondary impregnation of the present invention can significantly improve the mechanical strength and antioxidant properties of the graphite electrode, while ensuring that the impregnation slurry fully penetrates into the internal structure of the graphite electrode to form a tighter protective layer that effectively resists erosion from the external environment. The conductivity of the graphite electrode is further enhanced, and its use in industrial furnaces can significantly reduce energy consumption and improve production efficiency.

[0062] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a graphite electrode by secondary impregnation, characterized in that: The processing steps include: Preparing the impregnation slurry: the impregnation slurry includes a first impregnation slurry for impregnating the inner layer and a second impregnation slurry for impregnating the outer layer; The first impregnation slurry comprises 100-120 parts by weight of dry material, 35-45 parts by weight of binder, and 1-3 parts by weight of antioxidant; the dry material comprises 50-70wt% of petroleum coke, 20-40wt% of graphite chips, and 1-10wt% of raw chips; the binder is medium-temperature coal tar pitch or medium-temperature modified asphalt; the antioxidant is a composition of metal oxide, metal carbide, and metal boride in a mass ratio of 3:1:1; during preparation, the dry material is first preheated to 80-90°C, added to a kneading pot for dry mixing, and after mixing evenly, the antioxidant is added and stirred, and after stirring evenly, the binder is taken and heated to a melted state, and the softened binder is wet mixed with the dry mixture until a uniform paste is formed, so as to obtain the first impregnation slurry; The second impregnation slurry comprises 60-80 parts by weight of dry material, 25-35 parts by weight of binder and 7-15 parts by weight of low-quinoline medium-temperature coal tar pitch; the dry material comprises 30-50wt% of petroleum coke, 40-60wt% of graphite chips and 1-5wt% of raw chips, and the binder is medium-temperature coal tar pitch or medium-temperature modified asphalt; when preparing the second impregnation slurry, first preheat the dry material to 80-90°C, add it to a kneading pot for dry mixing, and after mixing evenly, take the binder and the low-quinoline medium-temperature coal tar pitch and heat them together until they are melted, and wet mix the softened binder with the dry mixture until a uniform paste is formed, so as to obtain the second impregnation slurry; Impregnation treatment: The surface of the graphite electrode green body is roughened, and after the treatment, the graphite electrode green body is placed in an impregnation tank; first, the inner layer is impregnated, that is, the green body is impregnated with the first impregnation slurry, and after the impregnation is completed, it is taken out and dried; then the outer layer is impregnated, that is, the green body that has been impregnated with the inner layer is impregnated with the second impregnation slurry, and after the impregnation is completed, it is taken out and dried; Drying treatment: Place the impregnated graphite electrode green body in a drying furnace for drying. The drying temperature is controlled at 100-120°C and the drying time is controlled at 12-24 hours to ensure that the solvent in the impregnation slurry is completely volatilized to form a uniform and dense impregnation layer. Sintering treatment: Place the dried graphite electrode green body in a sintering furnace for sintering. The sintering temperature is controlled at 1000-1200°C and the sintering time is controlled at 8-12 hours to ensure that the impregnation layer and the graphite electrode green body are fully combined to form a stable structure. Graphitization: Place the calcined product in an Acheson graphitization furnace and perform graphitization treatment according to the set power transmission curve, heat the temperature to 2500-3000°C, control the graphitization time to 10-20 hours, and then cool it to room temperature with the furnace and keep it for 150-300 hours to obtain a graphitized product; Cooling treatment: The obtained graphitized product is taken out from the Acheson graphitization furnace for trimming treatment to remove impurities and excess attached to the surface to obtain the final graphite electrode product.

2. The method for preparing a graphite electrode by secondary impregnation according to claim 1, characterized in that: When preparing the impregnation slurry, the particle sizes of the petroleum coke and the graphite powder used as the dry materials in the first impregnation slurry and the second impregnation slurry should be controlled between 100-200 mesh and 200-300 mesh, respectively.

3. The method for preparing graphite electrode by secondary impregnation according to claim 1, characterized in that: When preparing the impregnation slurry, the technical parameters of the medium-temperature coal tar or medium-temperature modified asphalt used as the dry material in the first impregnation slurry and the second impregnation slurry are a softening point between 80 and 120° C. and a needle penetration between 10 and 30.

4. The method for preparing graphite electrodes by secondary impregnation according to claim 1, characterized in that: When preparing the impregnation slurry, the oxide in the corresponding antioxidant is one or a combination of aluminum oxide, magnesium oxide, silicon oxide, and titanium oxide, the carbide is silicon carbide or boron carbide or a combination of the two, and the boride is titanium boride or zirconium boride or a combination of the two.

5. The method for preparing graphite electrode by secondary impregnation according to claim 1, characterized in that: In the stage of preparing the impregnation slurry, the viscosity of the obtained first impregnation slurry is between 3000mPa·S and 6000mPa·S; and the viscosity of the first impregnation slurry is between 1000mPa·S and 3000mPa·S.

6. The method for preparing graphite electrodes by secondary impregnation according to claim 1, characterized in that: During the impregnation process, the surface roughening of the graphite electrode green body can be achieved by methods such as sandblasting, mechanical grinding or chemical etching.

7. The method for preparing graphite electrodes by secondary impregnation according to claim 1, characterized in that: During the impregnation process, after the inner layer is impregnated with the first impregnation slurry and the outer layer is impregnated with the second impregnation slurry, the impregnation pressure and the impregnation time are different: During the inner layer impregnation, the impregnation pressure should be controlled at 0.1-0.3 MPa, and the impregnation treatment time should be 12-18 hours to ensure that the slurry can fully penetrate into the internal structure of the graphite electrode green body; After the outer layer is impregnated, the impregnation pressure should be appropriately increased to 0.3-0.5 MPa, and the impregnation treatment time should be 32-45 hours to form a denser outer protective film.

8. The method for preparing graphite electrodes by secondary impregnation according to claim 1, characterized in that: During the impregnation process, after the inner layer is impregnated with the first impregnation slurry and the outer layer is impregnated with the second impregnation slurry, a mold can be used to cold press and hold the outer side of the impregnated graphite electrode green body. During the cold pressing and holding, the corresponding mold temperature is lower than 60°C, the pressure is controlled at 0.5-1.0MPa, and the cold pressing holding time is controlled at 1-3 hours.

9. The method for preparing graphite electrodes by secondary impregnation according to claim 1, characterized in that: During the drying process, an inert atmosphere is used in the drying furnace to ensure the quality of the electrode. The drying temperature set in the drying furnace should be controlled between 100 and 150°C, and the drying time is 9 to 12 hours.